The Benefit of Diverse Fibre Prebiotics for Gut Health and Growth & Development - Jatiningrum Muaris, Hindah; Stephanie Kartjito, Melissa; Salsabila, Irma Nuraeni (Journal of Indonesian Specialized Nutrition, 2024)
Good gut health is essential to the well-being of the body, as the gut plays a role in digestion,nutrient absorption and immune system regulation. An imbalance in the gut microbiota can lead todigestive disorders, inflammation and decreased immunity. Prebiotics are compounds that cannot bedigested by the human body, but can be utilized by beneficial gut microorganisms, such as probioticbacteria. Prebiotics serve as a food source for good bacteria, support their growth, and maintain thebalance of gut microbiota. This review aims to discuss the benefits of fiber prebiotics, specifically FOS:GOS1:9 and Inulin, in supporting gut health and growth and development. The results showed that naturallyfounded prebiotics in various foods have an important role in promoting the growth of beneficial gutbacteria. Fiber prebiotics such as FOS:GOS 1:9 and Inulin act as “fertilizer” for benefical and nourishingthe gut microbiota, especially bifidobacteria and lactobacilli, which play a role in maintaining digestivehealth. These prebiotics help to improve the balance of the gut microbiota, which in turn supports ahealthy body. Proper dosing is essential for optimal benefits from prebiotics.